Mechanical properties and crack growth behavior in poled ferroelectric PMN-PZT ceramics - S. Jiansirisomboon (2018)
Ferroelectric lead magnesium niobate-lead zirconate titanate with the formula xPb(Mg1/3Nb2/3)O3-(1 - x)Pb(Zr0.52Ti0.48)O3where x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 was fabricated using a conventional mixed-oxide method. The densest ceramics were selected and some samples were subjected to electrical poling before mechanical investigation by indentation technique. In the poled ceramics, the growth of radial cracks was found to be dependent on the orientation of ferroelectric domains with respect to the poling direction. The crack length then showed significant anisotropy in the directions parallel and perpendicular to the poling which affected the KICvalues. However, the domain reorientation had no effect on HVvalues. The hardness tended to reduce with increasing mole ratio of PMN in the ceramics. The microstructure of the fracture surfaces revealed changes mainly of the intergranular fracture mode in the monolithic PMN and PZT to a mixed-mode of inter/transgranular fracture in the PMN-PZT ceramics. © 2005 Elsevier B.V. All rights reserved.